2018
DOI: 10.3389/fmars.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Matter Influences N2 Fixation in the New Caledonian Lagoon (Western Tropical South Pacific)

Abstract: Specialized prokaryotes performing biological dinitrogen (N 2 ) fixation ("diazotrophs") provide an important source of fixed nitrogen in oligotrophic marine ecosystems such as tropical and subtropical oceans. In these waters, cyanobacterial photosynthetic diazotrophs are well known to be abundant and active, yet the role and contribution of non-cyanobacterial diazotrophs are currently unclear. The latter are not photosynthetic (here called "heterotrophic") and hence require external sources of organic matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 68 publications
4
14
0
Order By: Relevance
“…Still, N 2 fixation models are mostly parameterized for Trichodesmium and its iron and phosphorus needs (Monteiro, Dutkiewicz and Follows 2011;Dutkiewicz et al 2012). The present study, and other recent studies (Benavides et al 2017(Benavides et al , 2018Rahav and Bar-Zeev 2017), indicate that taking the mixotrophic potential of diazotrophs into account will improve our understanding of their biogeography and seasonality. A development of biogeochemical models should in this context improve our ability to predict pools and fluxes of nitrogen in the global ocean.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Still, N 2 fixation models are mostly parameterized for Trichodesmium and its iron and phosphorus needs (Monteiro, Dutkiewicz and Follows 2011;Dutkiewicz et al 2012). The present study, and other recent studies (Benavides et al 2017(Benavides et al , 2018Rahav and Bar-Zeev 2017), indicate that taking the mixotrophic potential of diazotrophs into account will improve our understanding of their biogeography and seasonality. A development of biogeochemical models should in this context improve our ability to predict pools and fluxes of nitrogen in the global ocean.…”
Section: Resultssupporting
confidence: 61%
“…The undetectable nifH gene expression at this station is likely explained by the fact that our sampling took place at noon, while UCYN-B primarily express nifH at night (Church et al 2005b). UCYN (Benavides et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…4 b,c). Trichodesmium could have responded positively to DOP inputs as observed elsewhere 31 , 32 , but in our study DOP concentrations of clear and sewage waters were not significantly different (Table 1 ). We cannot exclude however, the possibility that there were toxic components in sewage waters that may have locally promoted the death of Trichodesmium close to the coast, as wastewaters are known to impair the metabolic activity of phytoplankton 33 .…”
Section: Resultssupporting
confidence: 61%
“…Finally, due to the inability of UCYN-A to fix inorganic carbon (Tripp et al, 2010), it is likely that the high abundance of the symbiosis in lagoon waters is sustained by photosynthates of the haptophyte host and/or labile dissolved organic matter input from the Dumbea River. Indeed, a recent study reported an increase in N 2 fixation rates and UCYN-A nifH gene expression in the mouth of the Dumbea River compared to waters located close to the reef (Benavides et al, 2018). Surprisingly, Trichodesmium abundances were lower than those of the UCYN-A symbiosis (Figure 4).…”
Section: Discussionmentioning
confidence: 87%